Definitions and assessments of physical literacy among children and youth: a scoping review - Martin Grauduszus; Stefanie Wessely; Marlen Klaudius; Christine Joisten (BMC, 2023)
Abstract Background Despite the recognised health benefits of physical activity, the physical activity levels of children and adolescents continue to decline. The concept of physical literacy (PL) is a promising holistic approach to physical activity promotion that addresses affective and cognitive domains in addition to physical and motor domains. In Germany, however, no uniform or widely used method exists for assessing PL in children. This research was conducted to compile information on international PL assessment systems for children and adolescents (up to 18 years of age), including their underlying definitions, structural designs and development processes, for the purpose of developing such a tool in Germany. Methods A scoping review was conducted using PubMed, Web of Science and SPORTDiscus database entries. The initial search was conducted in July 2022, with a follow-up search performed in May 2023. Articles that operationalised the construct of PL and at least two of the three domains were identified and included. The procedure and assessment tools used to evaluate the individual domains and the overall PL construct were extracted from all selected articles. Results A total of 882 articles were identified; five were added after a manual search. After duplicates were removed, 563 articles were screened by title and abstract, and 40 articles met the inclusion criteria and were included in the review. In a review of these articles, 23 different assessment procedures were identified. Eight assessment procedures included PL as a superordinate construct. Twenty-two of the 23 procedures assessed the affective and physical domains, only 14 assessed the cognitive domain. Conclusion Approximately half of the identified PL assessment systems addressed all three domains. Motor performance was most frequently integrated into the test procedures. Future developments in Germany should integrate all domains in the assessment to produce a holistic conceptualisation as the basis for appropriate funding.